2019
DOI: 10.1123/ijspp.2018-0766
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Playing Surface on Physical, Physiological, and Perceptual Responses to a Repeated-Sprint Ability Test: Natural Grass Versus Artificial Turf

Abstract: Purpose: The effect of playing surface on physical performance during a repeated-sprint ability (RSA) test and the mechanisms for any potential playing-surface-dependent effects on RSA performance are equivocal. The purpose of this study was to investigate the effect of natural grass (NG) and artificial turf (AT) on physical performance, ratings of perceived exertion, feeling scale, and blood biomarkers related to anaerobic contribution (blood lactate [Lac]), muscle damage (creatine kinase and lactate dehydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…A study using a 30 meter sprint as a performance indicator found a 16% difference in mean sprint times by a group of soccer players after performing a muscle fatiguing activity (Sanchez-Sanchez et al, 2014b). We found a similar sprint time reduction in our study, sprint performance for the male group was 11% slower following the agility course, whereas, females showed a 9% decrease in speed on the surface with less ER-%.Numerous studies have reported the effect of neuromuscular fatigue on high-intensity running activities (Lopez-Fernandez et al, 2018;Ammar et al, 2018;Chan et al, 2014). We adopted a similar method to IJKSS 8(4):42-50 determine if the MPs of the selected sports fields could influence neuromuscular fatigue.…”
Section: The Influence Of Time-dependent Surface Properties On Sprint Running Performance Between Male and Female Athletes 47supporting
confidence: 83%
See 1 more Smart Citation
“…A study using a 30 meter sprint as a performance indicator found a 16% difference in mean sprint times by a group of soccer players after performing a muscle fatiguing activity (Sanchez-Sanchez et al, 2014b). We found a similar sprint time reduction in our study, sprint performance for the male group was 11% slower following the agility course, whereas, females showed a 9% decrease in speed on the surface with less ER-%.Numerous studies have reported the effect of neuromuscular fatigue on high-intensity running activities (Lopez-Fernandez et al, 2018;Ammar et al, 2018;Chan et al, 2014). We adopted a similar method to IJKSS 8(4):42-50 determine if the MPs of the selected sports fields could influence neuromuscular fatigue.…”
Section: The Influence Of Time-dependent Surface Properties On Sprint Running Performance Between Male and Female Athletes 47supporting
confidence: 83%
“…Several other studies analyzed blood lactate changes following a bout of sport specific activities (Stone et al, 2016;Hughes et al, 2013) also reported no differences in performance between field types. Another study analyzing blood biomarkers found significant differences in running performance on different surfaces (Ammar et al, 2018). Blood specimen studies provide useful insight into blood-substrate differences after sprinting on AT and NG, unfortunately, the influence of the MPs of the testing fields could not be correlated with the blood-substrate concentration since the test fields were not examined.…”
Section: The Influence Of Time-dependent Surface Properties On Sprint Running Performance Between Male and Female Athletes 47mentioning
confidence: 99%